2009
DOI: 10.1016/j.jebo.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Choice, price competition and complexity in markets for health insurance

Abstract: The United States and other nations rely on consumer choice and price competition among competing health plans to allocate resources in the health sector. A great deal of research has examined the efficiency consequences of adverse selection in health insurance markets, less attention has been devoted to other aspects of consumer choice. The nation of Switzerland offers a unique opportunity to study price competition in health insurance markets. Switzerland regulates health insurance markets with the aim of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 21 publications
3
63
0
Order By: Relevance
“…Swiss research shows how the probability of switching is significantly lower in areas with larger numbers of insurers, even where premium variation is significant (23). Furthermore, among survey respondents who were very dissatisfied with their current insurer, 34% intended to switch in areas with fewer than 50 statutory health insurers versus 22% in areas with more than 50 insurers.…”
Section: Barriers To Consumer Mobilitymentioning
confidence: 97%
See 2 more Smart Citations
“…Swiss research shows how the probability of switching is significantly lower in areas with larger numbers of insurers, even where premium variation is significant (23). Furthermore, among survey respondents who were very dissatisfied with their current insurer, 34% intended to switch in areas with fewer than 50 statutory health insurers versus 22% in areas with more than 50 insurers.…”
Section: Barriers To Consumer Mobilitymentioning
confidence: 97%
“…Survey data from the Netherlands and Switzerland suggest many people feel no need to switch because they are satisfied with their current insurer (45% in the Netherlands and 79% in Switzerland) (22,23). There is also evidence of people preferring to maintain the status quo (24) or using subjective measures of quality to determine insurer choice.…”
Section: Switcher Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One could speculate that the decrease in sickness funds has even dampened the increase in switching rates due to less choice. On the other hand, Frank and Lamiraud (2009) have shown that more choice-more than 50 plans to choose from-may actually reduce enrollees' willingness to switch.…”
Section: [Insert Figures 5 and 6 About Here]mentioning
confidence: 99%
“…First, limited understanding is likely to lead to suboptimal decisions. Prior research has found that individuals often stick with the status quo, maintaining the same coverage they had in the past even when superior options are available, seek advice from family or friends who may also have low levels of health literacy, and commonly enroll in highly advertised plans or those with a well-known brand name (Frank and Lamiraud, 2009;Handel, 2011). If simplifying insurance reduced these tendencies, it could potentially improve the quality of choices.…”
Section: Consequences Of Consumers' Lack Of Understandingmentioning
confidence: 99%